Counselling for Career Construction Connecting life themes to construct life portraits: Turning pain into hope - Maree, J. G.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
In this book, career counselling history, best practices as well as contemporary models and methods are brought together. In reflecting on the past, present, and future of career counselling, the story of the postmodern, narrative or career construction approach and the model and methods used to advance careers in the 21st century is told. A meta-reflection concept is proposed, based on career construction principles and practices and aimed at providing an examination of repeated reflection in career counselling. Overall, an attempt is made to craft a text that is not just specifically instructive but also more generally so. Whereas the theory section includes much that is hands-on and practical, the inclusion of narratives in the practice section turns theory into practice. Narratives illustrate the complexity and contextuality of partnering with clients toward (re-)designed lives. Ultimately, the volume aims to demonstrate how Mark Savickas$1 (Bcounselling for career construction approach can be used by clients to connect life themes in order to construct life portraits under the guidance of counsellors.s
Keywords: Education; Education; Education (general).